How learning works : 8 research-based principles for smart teaching - Bridges, Michael W.; DiPietro, Michele; Lovett, Marsha; Norman, Marie K.; Ambrose, Susan A., 1958- (Jossey-Bass, 2023)
"we have expanded from seven to eight principles, which has allowed us to delve more deeply into the social and emotional components of learning. A brand new chapter (Chapter 1) explores individual differences among learners, and the intersections of identities and backgrounds that shape how students enter, respond to, and shape the learning environment. A reworked chapter (Chapter 7) investigates more fully the ways that instructors can shape the climate of their courses to make students feel included or marginalized -- and the implications for learning and performance. Across all eight principles, we updated the research previously discussed while integrating new areas of research. Wherever possible, we applied a diversity, equity, and inclusion lens, exploring issues of power, identity, and belonging as they relate to teaching and learning. We have also referenced a broader range of institution types and student populations than in the previous edition, and incorporated case studies and strategies relevant to emerging educational technologies and online and hybrid learning modalities."--